Evaluation of optimal dispersion conditions for CNT reinforced epoxy composites using cyclic voltammetry measurements. (4th May 2017) - Kwon, Dong-Jun; Shin, Pyeong-Su; Kim, Jong-Hyun; DeVries, K. Lawrence; Park, Joung-Man
Abstract : The optimum dispersion time of nanoparticles is important for obtaining uniform dispersion of fillers or other additives in a matrix. In this study, the optimal dispersion time of carbon nanotube (CNT) in a matrix was investigated using cyclic voltammetry (CV), measurement for different dispersion methods and times. In addition, the mechanical properties of CNT composites manufactured using different dispersion methods were evaluated by tensile and flexural tests. The CV and mechanical test results were correlated to the dispersion condition of CNT in the composites. It was found that tip-type sonication resulted in better dispersion than bath-type sonication. Improved CNT dispersion resulted in composites with both enhanced CV measurements and improved mechanical properties. In the study reported here, improvements in dispersion were generally accompanied by higher electrical currents. This suggests that the CV measurement method is an effective tool for determining optimal dispersion times, for different CNT dispersion processes.